Venture Capital Ecosystem in the Czech Republic : the Importance of Local and Foreign VC Investors in the Startup Financing Process - Červinka, David; Sankot, Ondřej, 1988-; Abdallah, Kareem Issam; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
The bachelor's thesis examines the Czech Republic's venture capital ecosystem, emphasizing the importance of domestic and international venture capital investors during the startup funding process. Within the analysis of the Czech VC ecosystem, descriptive and exploratory analyses of the data are used in combination with correlation analysis. Additionally, qualitative research is carried out in the form of semi-structured interviews with eight respondents from Czech venture capital firms. It has been discovered that local venture capital investors predominantly fund Czech startups during their early stages of development and that their involvement decreases with each subsequent fundraising round. Additionally, various reasons are identified for why local venture capital investors prefer to invest in the early stages of a startup's development, as well as why foreign venture capital investors, rather than local ones, fund startups at later stages.
Vedoucí práce: Ondřej Sankot
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses